2019
DOI: 10.4103/jhrs.jhrs_115_18
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum progesterone level on the day of ovulation trigger during In vitro fertilization and its effect on treatment outcome

Abstract: Background: Premature luteinization (PL) is defined as a premature rise in serum progesterone concentration on or before the day of ovulation trigger with human chorionic gonadotropin. The incidence of PL varies between 5% and 30% during in vitro fertilization and embryo transfer (IVF-ET). Materials and Methods: The prospective observational study comprising 380 patients undergoing IVF-ET. Blood samples were collected for serum progesterone le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Seven studies[ 29 30 31 32 33 34 35 ] have evaluated the impact of PPE on the live birth rate in fresh IVF cycles. Five studies have reported the impact on clinical pregnancy rate (CPR)[ 36 37 38 39 40 ] [ Table 1 ].…”
Section: P Remature P Rogesterone ...mentioning
confidence: 99%
“…Seven studies[ 29 30 31 32 33 34 35 ] have evaluated the impact of PPE on the live birth rate in fresh IVF cycles. Five studies have reported the impact on clinical pregnancy rate (CPR)[ 36 37 38 39 40 ] [ Table 1 ].…”
Section: P Remature P Rogesterone ...mentioning
confidence: 99%